Kualitas Jaringan Unit Pendaftaran Puskesmas Berdasarkan Delay - Eko Marjan; Rahyul Amri; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Network quality is the ability of an enterprise data network management system to meet or exceed user expectations by providing the desired functionality or desired information in a reliable, predictable, repeatable, and timely manner. The registration unit at the Puskesmas is a place to register or record the patient data to receive the health services they need. In this case, the registration of the patient's name at the Puskesmas will be recorded in the Simpus, which has been bridged with BPJS Healthy, so that patient data can be easily known about their history of health services that have been received. The Quality of the network in the Puskesmas' registration unit is evaluated with the Quality of Service (QoS) parameter where the Axence Net Tools 5 was used to measure the performance of the Network Link in the Puskesmas. In addition, network monitoring is done to determine the delay. Delay is the length of time required by the data to transfer information. It can be affected by physical media distance, congestion, or length of processing time. The delay measurement can be calculated by knowing the total time of data sending, then divided by the total packets data received, which is the TIPHON version of the delay category. The result of the study found that network quality of bridging P-Care and Simpus by using QoS Parametric in Delay was categorized as bad with total number 469ms. This means that the delay occurs because of congestion that uses network services exceeding the capacity that can be received by a data communication line and attenuation, which weakens the signal due to long distances.Keyword: Parameter QoS, Standart TIPHONE, Delay